Regional variability of glycemic control among adults with diabetes mellitus in Colombia - Nathaly Ramírez-García; Andrés Mauricio García-Sierra; Christian King; Ana Maria Valbuena-Garcia; Miguel Urina-Triana; Adalberto Quintero-Baiz; Lizbeth Alexandra Acuña-Merchan (Instituto Nacional de Salud Pública, 2022)
Not available